PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA FASE E SMAN 1 SOLOK SELATAN - Alhamdaniyah, Zahwa (Departemen Matematika, 2024)
Good communication skills are essential for learners. Inappropriate teaching practices have resulted in a lack of mathematics communication abilities among E phase students at SMAN 1 Solok Selatan. This issue can be resolved through problem-based learning. Mathematical communication skills were contrasted in this study with more conventional methods. This quasi-experimental research has a nonequivalent posttest-only control group design. During the 2023/2024 academic year, phase E students from SMAN 1 Solok Selatan made up the study's population. Simple Random Sampling was used to select the samples. The control group consisted of E7, while the experimental group consisted of E1. Afterwards, the kids' ability to express themselves mathematically was tested. Students' mathematics communication was enhanced through Problem-Based Learning. The null hypothesis (H0) was dismissed with a p-value of 0.016 (P-value < α) when the significance level was set at 0.05. Students' mathematical communication abilities are enhanced more effectively by Problem-Based Learning (PBL) compared to the usual learning model in SMAN 1 Solok Selatan Phase E.Keywords – Mathematical Communication Skills, Problem Based Learning Model, Conventional Model.